2015
DOI: 10.1063/1.4922538
|View full text |Cite
|
Sign up to set email alerts
|

Communication: One size fits all: Equilibrating chemically different polymer liquids through universal long-wavelength description

Abstract: Mesoscale behavior of polymers is frequently described by universal laws. This physical property motivates us to propose a new modeling concept, grouping polymers into classes with a common long-wavelength representation. In the same class, samples of different materials can be generated from this representation, encoded in a single library system. We focus on homopolymer melts, grouped according to the invariant degree of polymerization. They are described with a bead-spring model, varying chain stiffness and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…We have represented their data of the branch point diffusion with red dots in Figure . Because of widespread universality in polymer physics, an apples‐to‐apples comparison is possible between the two models, provided we rescale the units of measurement. Our reference point is the first peak of the g/t1/4 curve, signaling the departure from reptation (linear chain dynamics), to structurally slower inter‐star dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…We have represented their data of the branch point diffusion with red dots in Figure . Because of widespread universality in polymer physics, an apples‐to‐apples comparison is possible between the two models, provided we rescale the units of measurement. Our reference point is the first peak of the g/t1/4 curve, signaling the departure from reptation (linear chain dynamics), to structurally slower inter‐star dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…One famous example is the Kremer-Grest polymer model [128,129]. Zhang et al demonstrated that a melt of this phenomenological model can broadly be backmapped to many different types of homopolymers [130]. Everaers et al recently matched the generic large-scale behavior of Kremer-Grest simulations to chemistry-specific experiments via the Kuhn length [131].…”
Section: Compositional Samplingmentioning
confidence: 99%
“…The soft-sphere model proposed for the PS is motivated by arguments [22,29,30,32] based on general polymer physics. The model aims to capture long-wavelength conformational and structural properties of PS melts, accurately enough for performing backmapping at one state point.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Melts with the sameN form a single class of materials which can be described [29] (in renormalized space) by a single blob-based model. This common model can be used to inter-convert [29] chemically different materials within the sameN -class. Increasing N b has two important consequences: a) the conformations of subchains approach the Gaussian statistics of ideal random-walks and b) the correlation hole of blobs becomes more shallow, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation